The impact of green finance on carbon emission intensity in China: mediating and spatial effects - Xiaonan Liu; Jinglei Lu; Bin Zhou (Frontiers in Environmental Science)
IntroductionInvestigating the relationship between green finance and carbon emission intensity is essential for understanding its role in China’s carbon reduction strategy.MethodsThis study employs the entropy weight method to measure the green finance development index across 30 Chinese provinces.Using double fixed-effects, mediation effect, and Spatial Durbin Models (SDM), the analysis reveals three key findings.ResultsFirstly, green finance directly reduces carbon emission intensity and indirectly does so by fostering technological innovation and optimizing energy structures, with more pronounced effects in western regions, highlighting regional disparities. Secondly, green finance shows a significant spatial spillover effect, reducing carbon emission intensity in neighboring provinces, beyond the impact on economically and geographically similar regions. Lastly, environmental regulation intensity positively influences carbon emission intensity in all models.DiscussionThese findings deepen our understanding of green finance’s role in China’s carbon reduction efforts and provide strong theoretical support for policy formulation, demonstrating its critical role in environmental governance and sustainable development.